Comparative Review of Worship Spaces in Buddhist and Cistercian Monasteries: The Three Temples of Guoqing Si (China) and the Church of the Royal Abbey of Santa Maria de Poblet (Spain) - Weiqiao Wang (MDPI AG, 2021)
Although the two parallel architectural forms, Han Buddhists and the Cistercian monasteries, seem, on the surface, to be very different—belonging to different religions, different cultural backgrounds, and different ways of construction—they share many similarities in the internal institutional model of monks’ lives and the corresponding architectural core values. The worship space plays the most significant role in both monastic life and layout. In this study, the Three Temples of Guoqing Si and the Church of the Royal Abbey of Santa Maria de Poblet are used as examples to elucidate the connotations behind the architectural forms, in order to further explore how worship spaces serve as an intermediary between deities, monks, and pilgrims. Based on field research and experience of monastic life, this comparative study highlights two fundamental similarities between the Three Temples and the Church: First, both worship spaces are derived from imperial prototypes, have a similar priority of construction, occupy the most important place in both sacred venues, and both serve as a reference for the development of monastic layout. Second, both worship spaces are composed of a similar programmed functional layout, including similar space dominators as well as itineraries. Beyond the surface similarities, this article further analyzes the reasons behind the three differences found. Due to their different understanding of deities, both worship spaces show different ways of worship, images of deities, and distances towards them.